COVID-19 Pandemic and Pediatric Type 1 Diabetes: No Significant Change in Glycemic Control During The Pandemic Lockdown of 2020 - Nwosu, Benjamin Udoka; Al-Halbouni, Layana; Parajuli, Sadichchha; Jasmin, Gabrielle; Zitek-Morrison, Emily; Barton, Bruce A. (Frontiers in Endocrinology, 2021)
Importance: There is no consensus on the impact of the 2020 COVID-19 pandemic lockdown on glycemic control in children and adolescents with type 1 diabetes (T1D) in the US. Aim: To determine the impact of the pandemic lockdown of March 15th through July 6th, 2020 on glycemic control after controlling for confounders. Subjects and Methods: An observational study of 110 subjects of mean age 14.8 ± 4.9 years(y), [male 15.4 ± 4.0y, (n=57); female 14.1 ± 3.8y, (n=53), p=0.07] with T1D of 6.31 ± 4.3y (95% CI 1.0-19.7y). Data were collected at 1-4 months before the lockdown and 1-4 months following the lifting of the lockdown at their first post-lockdown clinic visit. Results: There was no significant change in A1c between the pre- and post-pandemic lockdown periods, 0.18 ± 1.2%, (95% CI -0.05 to 0.41), p=0.13. There were equally no significant differences in A1c between the male and female subjects, -0.16 ± 1.2 vs -0.19 ± 1.2%, p=0.8; insulin pump users and non-pump users, -0.25 ± 1.0 vs -0.12 ± 1.4%, p=0.5; and pubertal vs prepubertal subjects, 0.18±1.3 vs -0.11 ± 0.3%, p=0.6. The significant predictors of decrease in A1c were pre-lockdown A1c (p<0.0001) and the use of CGM (p=0.019). The CGM users had significant reductions in point-of-care A1c (0.4 ± 0.6%, p=0.0012), the CGM-estimated A1c (p=0.0076), mean glucose concentration (p=0.022), a significant increase in sensor usage (p=0.012), with no change in total daily dose of insulin (TDDI). The non-CGM users had significantly increased TDDI (p<0.0001) but no change in HbA1c, 0.06 ± 1.8%, p=0.86. Conclusions: There was no change in glycemic control during the pandemic lockdown of 2020 in US children.